2022
DOI: 10.55002/mr.2.5.34
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of chicken meatball quality through NIR spectroscopy and multivariate analysis

Abstract: Near Infrared (NIR) Spectroscopy leads a great opportunity to replace the expensive and time-consuming chemical conventional analysis for determination of the quality of meat products. This study was conducted aiming to evaluate the feasibility of NIRS and to establish a rapid assessment method to easily predict the quality of chicken meatball. Samples of meatball (n=123) were collected from Golden Harvest Company of Bangladesh. After collecting sample, spectra were obtained prior to analysis and a total of 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…In Table 2, NIRS calibration and prediction statistics for different parameters is shown. A wide and even distribution in composition, along with precise reference analysis techniques are recognized as important characteristics of the calibration set of samples, in order to obtain a successful equation (Hashem et al, 2022a(Hashem et al, , 2022b(Hashem et al, and 2022cCen and He, 2007). Calibration co-efficient were 0.979, 0.978, 0.986, 0.977, 0.965, 0.967, 0.975 for DM, Moisture, CP, EE, CF and ash, respectively, where Egesel and Kahriman, (2012) showed that CP, EE, ash for maize grain were 0.990, 0.823, 0.926 respectively.…”
Section: Nirs Calibration and Prediction Statistics For Different Par...mentioning
confidence: 99%
“…In Table 2, NIRS calibration and prediction statistics for different parameters is shown. A wide and even distribution in composition, along with precise reference analysis techniques are recognized as important characteristics of the calibration set of samples, in order to obtain a successful equation (Hashem et al, 2022a(Hashem et al, , 2022b(Hashem et al, and 2022cCen and He, 2007). Calibration co-efficient were 0.979, 0.978, 0.986, 0.977, 0.965, 0.967, 0.975 for DM, Moisture, CP, EE, CF and ash, respectively, where Egesel and Kahriman, (2012) showed that CP, EE, ash for maize grain were 0.990, 0.823, 0.926 respectively.…”
Section: Nirs Calibration and Prediction Statistics For Different Par...mentioning
confidence: 99%
“…Among the essential nutrients protein is the major as it plays the vital role in body building but majority of the population in developing countries is suffering from protein shortage (Apata et al, 2011). Meat and meat products can minimize this problem as a contributor of high-quality protein (Hashem et al, 2021(Hashem et al, , 2022(Hashem et al, and 2023Hasan et al, 2022;Hossain et al, 2021 andTalukdar et al, 2014). Among the processed meat products e.g.…”
Section: Introductionmentioning
confidence: 99%